2020
DOI: 10.1101/2020.08.29.20184473
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entry screening and multi-layer mitigation of COVID-19 cases for a safe university reopening

Abstract: We have performed detailed modeling of the COVID-19 epidemic within the State of Illinois at the population level, and within the University of Illinois at Urbana-Champaign at a more detailed level of description that follows individual students as they go about their educational and social activities. We ask the following questions: (1) How many COVID-19 cases are expected to be detected by entry screening? (2) Will this initial bump in cases be containable using the mitigation steps being undertaken at UIUC?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Those strategies were combined with regular testing to rapidly detect and quarantine infected students. Previous modeling studies have investigated different aspects of COVID-19 spread on college campuses [2][3][4][5][6][7]. For example, Paltiel et al [8] used a simple homogeneous mixing SEIR compartmental model to evaluate the effectiveness of screening strategies in a college with 5000 students; Weeden and Gornwell [9] designed student contact networks though transcript data and used these networks to studied the effectiveness of small course enrollments on reducing the risk of epidemic spread.…”
Section: Introductionmentioning
confidence: 99%
“…Those strategies were combined with regular testing to rapidly detect and quarantine infected students. Previous modeling studies have investigated different aspects of COVID-19 spread on college campuses [2][3][4][5][6][7]. For example, Paltiel et al [8] used a simple homogeneous mixing SEIR compartmental model to evaluate the effectiveness of screening strategies in a college with 5000 students; Weeden and Gornwell [9] designed student contact networks though transcript data and used these networks to studied the effectiveness of small course enrollments on reducing the risk of epidemic spread.…”
Section: Introductionmentioning
confidence: 99%
“…For universities and colleges, test allocation needs to be customized according to the local disease rates and community testing capacity [18], as are often characterized by the budget for testing, the total number of tests available, the observed number of positive tests and test positive rate ( Table S4 ). As tests of different costs and accuracy become available, thequestion of test allocation becomes even more challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Extension to allocating two tests. For universities and colleges, test allocation needs to be customized according to the local disease rates and community testing capacity [18], as are often characterized by the budget for testing, the total number of tests available, the observed number of positive tests and test positive rate (Table S4) [19,20,22]. Mirroring current market information, we set the price for the rapid antigen test and for the RT-PCR test as $5 and $135, respectively, and we assume test sensitivity values are 0.45 and 0.9, respectively [22,21].…”
Section: Figure 2 a And B Corresponds To The Setting With Limited Numbementioning
confidence: 99%
“…Previous studies modeling university populations did not account for infections in the broader off-campus community. 20-24 However, we have shown that including the general population when modeling COVID-19 transmission on university campuses is critical, since this population bears the brunt of the incremental morbidity and mortality burden of COVID-19. As a result, university policies that either discourage student return to the community, 54 such as offering coursework fully online, or mitigate COVID-19 risks for students returning to campus, such as screening for COVID-19 symptoms and routine COVID-19 testing in asymptomatic individuals, can have substantial impacts on the city’s COVID-19 burden.…”
Section: Discussionmentioning
confidence: 99%
“…Given the unique features of university communities, several studies have modeled COVID-19 transmission dynamics specifically on university campuses and evaluated potential mitigation strategies. 18,20-24 These studies used mathematical models of viral transmission dynamics, tailored to reflect a university context, in order to evaluate testing and contact tracing strategies, largely focusing on the question of how frequently to test asymptomatic students. All analyses concluded that frequent testing (sometimes multiple times a week) would be needed to contain COVID-19 outbreaks on campus.…”
Section: Introductionmentioning
confidence: 99%